Efektivitas Metode Drill dalam Pembelajaran Vokasional Seni Tari Di SLBN 2 Padang - Selvi Rahmadani Pratiwi (Universitas Indraprasta PGRI, 2026)
This study aims to evaluate the effectiveness of the Drill Method in improving the activities and learning outcomes of mildly disabled students in vocational dance subjects in class XI.C SLB N 2 Padang. The research used a Classroom Action Research (PTK) approach carried out in two cycles with a subject of seven students. The research instruments included learning outcome tests and learning activity observation sheets, while the data were analyzed using percentage techniques. The results showed an increase in student learning activities from 53.8% in cycle I to 91% in cycle II. The average value of psychomotor learning outcomes also increased from 70 in cycle I to 87.1 in cycle II, with learning completeness increasing from 42.8% to 85.7%. These findings confirm that the Drill Method is effective in increasing student engagement, motivation and learning outcomes, while making dance learning more active and fun.